The future of women and youths in the bean transformation agenda in Sub-Saharan Africa - Nchanji, Eileen Bogweh (Pan-Africa Bean Research Alliance, 2018)
The call for a bean transformative agenda is led by the Pan-African Bean Alliance (PABRA). It aims to position common bean as a commercial crop, though it is still grown for home consumption. They have designed and put in place gender sensitive interventions aimed at increasing women and youths access to innovative technology, support services, credit and markets. Thus reducing gender inequity and creating an enabling business environment for beans production and business.